Estimates of Household Food Waste by Categories and Their Determinants: Evidence from China - Xiaolei Li; Yi Jiang; Ping Qing (Foods, 2023)
Household food waste has become a global concern for all countries in the world. This study focuses on the household level to clarify the impact of household food waste, and we use an online questionnaire survey across China to estimate the proportion of household food waste from five categories, including whole food; fruits and vegetables; poultry, eggs, meat, and dairy products; staple food; and snacks and candy. Then, we use the logit and Tobit models to estimate the relationship between the five food categories and consumer characteristics. First, the statistical analysis shows that in China, the incidence rate and proportion of household food waste are 90.7% and 9.9%, respectively. Among them, the incidence rate and proportion of fruit and vegetable waste are the highest. The results of heterogeneity also show regional differences in the incidence rate and proportion of food waste. Second, the empirical results show that label cognition, garbage disposal cognition, vegetarianism, population, children or elders in the household, the experience of starvation, and age are important explanatory factors for the incidence and proportion of food waste in the household.